Differences in Host Cell Invasion and Salmonella Pathogenicity Island 1 Expression between Salmonella enterica Serovar Paratyphi A and Nontyphoidal S. Typhimurium - Elhadad, Dana (Infect Immun, 2016)
Active invasion into nonphagocytic host cells is central to Salmonella enterica pathogenicity and dependent on multiple genes within Salmonella pathogenicity island 1 (SPI-1). Here, we explored the invasion phenotype and the expression of SPI-1 in the typhoidal serovar S. Paratyphi A compared to that of the nontyphoidal serovar S. Typhimurium. We demonstrate that while S. Typhimurium is equally invasive under both aerobic and microaerobic conditions, S. Paratyphi A invades only following growth under microaerobic conditions. Transcriptome sequencing (RNA-Seq), reverse transcription-PCR (RT-PCR), Western blot, and secretome analyses established that S. Paratyphi A expresses much lower levels of SPI-1 genes and secretes lesser amounts of SPI-1 effector proteins than S. Typhimurium, especially under aerobic growth. Bypassing the native SPI-1 regulation by inducible expression of the SPI-1 activator, HilA, considerably elevated SPI-1 gene expression, host cell invasion, disruption of epithelial integrity, and induction of proinflammatory cytokine secretion by S. Paratyphi A but not by S. Typhimurium, suggesting that SPI-1 expression is naturally downregulated in S. Paratyphi A. Using streptomycin-treated mice, we were able to establish substantial intestinal colonization by S. Paratyphi A and showed moderately higher pathology and intestinal inflammation in mice infected with S. Paratyphi A overexpressing hilA. Collectively, our results reveal unexpected differences in SPI-1 expression between S. Paratyphi A and S. Typhimurium, indicate that S. Paratyphi A host cell invasion is suppressed under aerobic conditions, and suggest that lower invasion in aerobic sites and suppressed expression of immunogenic SPI-1 components contributes to the restrained inflammatory infection elicited by S. Paratyphi A.